Influence of Powder-to-Gel Ratio on Physicochemical Properties of a Calcium Silicate Sealer - Torres, Fernanda F. E. [UNESP]; Perinoto, Patricia [UNESP]; Bosso-Martelo, Roberta; Chavez-Andrade, Gisselle M. [UNESP]; Guerreiro-Tanomaru, Juliane M. [UNESP]; Tanomaru-Filho, Mario [UNESP] (Univ Costa Rica, Fac Odontologia, 2020)
Differences in liquid-to-powder ratio can affect the properties of calcium silicate-based materials. This study assessed the influence of powder-to-gel ratio on physicochemical properties of NeoMTA Plus. Setting time (minutes), flow (mm and mm(2)), pH (at different periods), radiopacity (mm Al) and solubility (% mass loss) were evaluated using the consistencies for root repair material (NMTAP-RP; 3 scoops of powder to 2 drops of gel) and root canal sealer (NMTAP-SE; 3 scoops of powder to 3 drops of gel), in comparison to Biodentine cement (BIO) and TotalFill BC sealer (TFBC). Statistical analysis was performed using one-way ANOVA and Tukey tests (alpha=0.05). BIO had the shortest setting time, followed by NMTAP-RP and NMTAP-SE. TFBC showed the highest setting time and radiopacity. BIO, NMTAP-RP, and NMTAP-SE had similar radiopacity. All materials promoted an alkaline pH. NMTAP-RP/SE presented lower solubility than BIO and TFBC. Regarding the flow, TFBC had the highest values, followed by NMTAP-SE, and NMTAP-RP. BIO had the lowest flow. In conclusion, NMTAP in both powder-to-gel ratios showed high pH and low solubility. The increase in the powder ratio decreased the setting time and flow. These findings are important regarding the proper consistency and work time to clinical application.
Keywords: Calcium silicate; Dental materials; Endodontics; Physicochemical properties; Root canal sealer; Root repair material